Singular Semiotic in the Models of Aljwahere - جريكوس, تيسير; شياني, بانا; يونس, محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study is an attempt to highlight the impact that pumping vocabulary in the composition of poetry, and is no doubt that the semiotic this vocabulary effectively contribute in giving a recipe poetic text, because they represent the signs of semantics as diverse contexts in which they are contained, and the dynamism achieved from a damaged vocabulary within the same topic opens up new horizons, and pave the way for a variety of readings, according to the ability of the recipient language, cognitive and proceeds, hence the emphasis on the singular in construction as a key text for reproduction again.